E-commerce and web technologies : 16th International Conference on Electronic Commerce and Web Technologies, EC-Web 2015, Valencia, Spain, September 2015, revised selected papers /: 16th International Conference on Electronic Commerce and Web Technologies, EC-Web 2015, Valencia, Spain, September 2015, revised selected papers. (2015) - Unknown
No abstract available